The Effect of Endurance Training with Flax Seed on Cortisol and Lipid Profile of Obese Women - Alireza Pazoki; Sajad Arshadi (Islamic Azad University, 2017)
Introduction: Obesity is one of the global health problems that causes tissue damage and mortality due to hormonal changes and increased inflammatory markers and metabolic syndrome indices. For this reason, this study was conducted to investigate changes of endurance training with flax seed on cortisol concentration and lipid profile of obese women. Methods: In the present study, 48 obese women aged 30-40 years old were randomly divided into four groups of 12, including 1. Endurance training, 2. Flaxseed supplementation, 3. Endurance training with flaxseed supplementation and 4. Control. Groups 1 and 3 performed endurance training for 8 weeks and 3 sessions per week at 40-70% of maximum heart rate, group 2 consume 6 grams flax seed daily and group 4 did not have any exercise and flaxseed consumption. Blood samples were measured before and after 8 weeks of endurance training and flax seed consumption. To analyze the data, descriptive and inferential tests of one-way ANOVA, Tukey' s post hoc, and paired sample t-tests were used at the significance level of 0.05. Results: The results showed a significant difference in endurance training, endurance training with flax seed and control groups also showed a non-significant difference in flax seed group in cholesterol (p=0.003, p=0.001, p<0.001, p=0.065 respectively), triglyceride (p=0.002, p=0.001, p=0.01, p=0.12 respectively) and LDL (p=0.008, p=0.003, p=0.028, p=0.091 respectively) HDL (p=0.011, p=0.014, p=0.031, p=0.26 respectively), also based on the findings of the study, non-significant differences were found between the levels of cortisol in the research groups (p=0.26, p=0.12, p=0.18, p=0.75 respectively). Conclusion: It seems that endurance trainings with flax seed can improve the lipid profiles of obese women.